-7p-39=5(-5p+30)

Simple and best practice solution for -7p-39=5(-5p+30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7p-39=5(-5p+30) equation:


Simplifying
-7p + -39 = 5(-5p + 30)

Reorder the terms:
-39 + -7p = 5(-5p + 30)

Reorder the terms:
-39 + -7p = 5(30 + -5p)
-39 + -7p = (30 * 5 + -5p * 5)
-39 + -7p = (150 + -25p)

Solving
-39 + -7p = 150 + -25p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '25p' to each side of the equation.
-39 + -7p + 25p = 150 + -25p + 25p

Combine like terms: -7p + 25p = 18p
-39 + 18p = 150 + -25p + 25p

Combine like terms: -25p + 25p = 0
-39 + 18p = 150 + 0
-39 + 18p = 150

Add '39' to each side of the equation.
-39 + 39 + 18p = 150 + 39

Combine like terms: -39 + 39 = 0
0 + 18p = 150 + 39
18p = 150 + 39

Combine like terms: 150 + 39 = 189
18p = 189

Divide each side by '18'.
p = 10.5

Simplifying
p = 10.5

See similar equations:

| 3y+6x=360 | | 10x^2-17x+34=7x^2-26x+28 | | -15+-14e=-33 | | -13-8j=-5 | | 9m+6=96# | | 4b+6=-22 | | 4(p+5)=2 | | -43=13p-65 | | 0=x^4+4x^2-32 | | y=(-8)(1) | | (X+10)(x)=144 | | 21-4j=13 | | 11-3*3-1= | | -2(x+y)+9=1 | | -7=6m-7m | | 6(X-1)=2x+6 | | (x-2)*(x+3)=x*x-8 | | 17d-5=3d | | y=-16t^2+468 | | 2x-13-6x+3=28-4-2-3x | | 20+1x=25+.75x | | 7+v(1)=6+v | | 9-5m+2=7+2m | | 9n-9=-126 | | 45=3 | | 16c+8=3c | | -9-6g=-33 | | Sen(4x)-cos(4x)-1=0 | | -6+p=14 | | 9*243= | | 66=2.2X | | 2x+7+6x= |

Equations solver categories